TRANSITIVITY ANALYSIS ON INDONESIAN SLOGANS OF COVID 19 IN INSTAGRAM - Widyashanti Kunthara Anindita; Yunita Widiyantari; Rizka Hayati (Jurnal CULTURE (Culture, Language, and Literature Review), 2022)
This paper has the following purposes: (1) to examine the sum of phrases, clauses and complex sentences used in Indonesian slogans related to corona virus in Indonesia in five instagram accounts, 2) to recognize the words often used in Indonesian slogans related to corona virus in Indonesia in five instagram accounts, 3) to elaborate the idea of those slogans presented by using ideational metafunction. The data were accumulated by gathering 40 slogans from five instagram accounts. The results of the study were as follows: 1) the most often used keywords were covid, korona, dengan, yang, successively 2) the most often used constituents of the ideational metafunctional were participant, and followed by processes and circumstances successively and 3) the most often used sub-component of participant was goal, the most often used sub-component of process was material creative and the most often used sub-component of circumstance is manner means.